Sawtooth mitigation in 3D MHD tokamak modelling with applied magnetic perturbations. (3rd November 2016) - Bonfiglio, D; Veranda, M; Cappello, S; Chacón, L; Escande, D F
Abstract: The effect of magnetic perturbations (MPs) on the sawtoothing dynamics of the internal kink mode in the tokamak is discussed in the framework of nonlinear 3D MHD modelling. Numerical simulations are performed with thepixie 3d code (Chacón 2008 Phys. Plasmas 15 056103) based on a D-shaped configuration in toroidal geometry. MPs are applied as produced by two sets of coils distributed along the toroidal direction, one set located above and the other set below the outboard midplane, like in experimental devices such as DIII-D and ASDEX Upgrade. The capability of n   =  1 MPs to affect quasi-periodic sawteeth is shown to depend on the toroidal phase difference Δ ϕ between the perturbations produced by the two sets of coils. In particular, sawtooth mitigation is obtained for the Δ ϕ = π phasing, whereas no significant effect is observed for Δ ϕ = 0 . Numerical findings are explained by the interplay between different poloidal harmonics in the spectrum of applied MPs, and appear to be consistent with experiments performed in the DIII-D device. Sawtooth mitigation and stimulation of self-organized helical states by applied MPs have been previously demonstrated in both circular tokamak and reversed-field pinch (RFP) experiments in the RFX-mod device, and in related 3D MHD modelling.